Choline-based ionic liquids as media for the growth of Saccharomyces cerevisiae - Sivapragasam, Magaret; Wilfred, Cecilia Devi; Jaganathan, Joshua Raj; Krishnan, Sooridarsan; Wan Ab. Karim Ghani, Wan Azlina (MDPI, 2019)
Ionic liquids (ILs) have garnered great attention as alternative solvents in many biological reactions and applications. However, its unknown toxicity is in line with the challenges to use it for biological applications. In this study, three choline based Ionic Liquids—choline saccharinate (CS), choline dihydrogen phosphate (CDHP), and choline tryptophanate (CT) were assessed for their suitability on the growth of Saccharomyces cerevisiae. The ILs were incorporated into the growth media of S. cerevisiae (defined as synthetic media) to access its potential as a substitute to conventional media. The compatibility of the synthetic media was evaluated based on the toxicity (EC50), growth curve, and glucose profile. The results showed that the incorporation of CDHP and CS did promote the growth of S. cerevisiae with a rapid glucose consumption rate. The growth of S. cerevisiae with the media composition of yeast extract, peptone, and CS showed improvement of 13%. We believe that these observations have implications in the biocompatibility studies of ILs to microorganisms.